Virions at the gates: receptors and the host-virus arms race. - John M Coffin (PLoS Biology, 2013)
All viruses need to bind to specific receptor molecules on the surface of target cells to initiate infection. Virus-receptor binding is highly specific, and this specificity determines both the species and the cell type that can be infected by a given virus. In some well-studied cases, the virus-binding region on the receptor has been found to be unrelated to the receptor's normal cellular function. Resistance to virus infection can thus evolve by selection of mutations that alter amino acids in the binding region with minimal effect on normal function. This sort of positive selection can be used to infer the history of the host-virus "arms race" during their coevolution. In a new study, Demogines et al. use a combination of phylogenetic, structural, and virological analysis to infer the history and significance of positive selection on the transferrin receptor TfR1, a housekeeping protein required for iron uptake and the cell surface receptor for at least three different types of virus. The authors show that only two parts of the rodent TfR1 molecule have been subject to positive selection and that these correspond to the binding sites for two of these viruses-the mouse mammary tumor virus (a retrovirus) and Machupo virus (an arenavirus). They confirmed this result by introducing the inferred binding site mutations into the wild-type protein and testing for receptor function. Related arenaviruses are beginning to spread in human populations in South America as the cause of often fatal hemorrhagic fevers, and, although Demogines et al. could find no evidence of TfR1 mutations in this region that might have been selected as a consequence of human infection, the authors identified one such mutation in Asian populations that affects infection with these viruses.